Quality of care in adults aged over 60 in stages other than their own home - Olga Lidia Banda González; Cinthya Patricia Ibarra González; Guadalupe Vázquez Salazar; Laura Roxana de los Reyes Nieto (Universidad de Alicante, 2012)
At present, human beings get more and more aged in a better estate of health, but the consequence of that fact implies wider possibilities of being submitted to more chronic illnesses and disabilities, (Bazo, 1998). In this respect, Lehr (1993) states that the hope for a good life not only means a longer life but a better quality of life. It is not how old a person could get but how he gets old, how does he age. Thus, the adult should be given better care in order to keep him in a good health condition with an interesting quality of life. A research was done to discover the quality of care an adult gets when he lives in a different stage of his own home, his own environment, in a "Home". A formal, observational, descriptive, transversal study was run where the unit to be analyzed was an adult between 60 and 75 years of age. Results showed that care provided to an aged adult in a stage other than his own home only contributes either to maintain his physical capacities or to perform his daily life activities, which in our opinion is not enough to be considered as "a quality of life" care.